Associação entre o tempo de contato na prática educativa e seu impacto no conhecimento, atitude e autocuidado em diabetes mellitus - Mariana Almeida Maia (2015)
This is a longitudinal study of quantitative basis, and aimed to investigate the association between contact time in the educational practices and knowledge levels, psychological attitude and self-care in diabetes Mellitus. The study had the participation of 151 users with diabetes linked to Health Strategies of Belo Horizonte Family, during the years 2012 and 2013. The educational process had four cycles lasting one month and three-month interval between each cycle. The topics were on the pathophysiology of the disease, healthy eating, physical activity, development of goals for the performance of self-care practices and coping of care barriers of the disease. The themes were developed through play and interactive dynamics, which included the participation of health professionals from the basic units. The educational process had three strategies approach: group education, home visits and telephone intervention. The instruments were applied: Knowledge Questionnaire in Diabetes (DKN-A), Psychological Attitude Questionnaire (ATT-19) and Questionnaire Care in Diabetes Self-Management (ESM) at baseline (T0) and end time (FT). We used the Student's t-test paired to compare the mean scores and the T0 TF times and the Student t test for independent samples to compare the mean differences of scores in the different contact time intervals. The significance level was 0.05%. It is noteworthy that 116 (76.8%) participants were female, aged between 39 and 83 years (mean 64.1 years, SD = 9.80). The majority lived with a partner (52.3%) had progression of the disease less than 10 years (56.3%) and 77.5% of users declared inactive for occupation. After the educational process, it was possible to detect statistically significant differences in mean levels of knowledge about the disease, psychological attitude and self-management of care in diabetes compared to baseline average. To the level of knowledge about the disease, there was a statistically significant increase in mean score of the DKN-A (mean difference: 1:47). Regarding the psychological attitude, there was a statistically significant decrease in the mean score of the ATT-19 (mean difference: -14.77). Both the knowledge as to the psychological attitude, it was not possible to identify a value for the contact time from which could be observed changes in average levels of scores. As for the self-care scores, the difference in the average level of the users who participated in the educational intervention for 8 hours or more was statistically greater than the difference in the average level of those who participated for less than 8 hours (0.67 ± 1:55 ± 1:30 against 0:19 respectively; p-value <0.05). Thus, for the effectiveness of development of variables to control the disease, it is necessary to consider the contact time as a relevant factor for the development of the educational process.